2015
DOI: 10.1002/jae.2495
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Granger Causality: Guidelines for Multivariate Analysis

Abstract: Summary We propose an extension of the bivariate nonparametric Diks–Panchenko Granger non‐causality test to multivariate settings. We first show that the asymptotic theory for the bivariate test fails to apply to the multivariate case, because the kernel density estimator bias and variance cannot both tend to zero at a sufficiently fast rate. To overcome this difficulty we propose to reduce the order of the bias by applying data sharpening prior to calculating the test statistic. We derive the asymptotic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Their findings further revealed that physical capital and energy are two significant contributors to the economic growth in Asian Pacific countries. Similarly, Fang and Wolski () examined the causal relationship between energy consumption, human capital and economic growth in China during the period of 1965–2014 using the recently developed nonlinear multivariate Granger causality test by Diks and Wolski (). Their findings revealed that there is no causal relationship between aggregate energy use and coal, natural gas and hydroelectricity consumption, while unidirectional causality running from GDP to oil is found using the nonlinear approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings further revealed that physical capital and energy are two significant contributors to the economic growth in Asian Pacific countries. Similarly, Fang and Wolski () examined the causal relationship between energy consumption, human capital and economic growth in China during the period of 1965–2014 using the recently developed nonlinear multivariate Granger causality test by Diks and Wolski (). Their findings revealed that there is no causal relationship between aggregate energy use and coal, natural gas and hydroelectricity consumption, while unidirectional causality running from GDP to oil is found using the nonlinear approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, we test whether there exists cointegration among them. Finally, we apply linear and non-linear causality tests using the recently developed method by [27] (hereafter DW test).…”
Section: Econometrics Methodologymentioning
confidence: 99%
“…Our final step is to check for the presence of nonlinear causal relationships between the variables. For this purpose, we employ the test of [27], which is a nonparametric test. The no parametrization implies testing non-Granger-causality against an unspecified alternative.…”
Section: Nonlinear Causality Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, all of the aforementioned tests are designed for investigating the linear dependence (i.e., the cross-correlation in the mean, variance or higher moments) between two model residuals, and hence they could exhibit a lack of power in detecting the non-linear dependence structure. A significant body of research so far has documented the non-linear dependence relationship among a myriad of economic fundamentals; see, e.g., Hiemstra and Jones (1994), Wang Diks and Wolski (2016) to name a few. However, less attempts have been made in the literature to account for both linear and nonlinear dependence structure, which shall be two parallel important characteristics to be tested.…”
mentioning
confidence: 99%